PENERAPAN APLIKASI FIGMA TERHADAP PERTIMBANGAN LAYANAN USER INTERFACE/USER EXPERIENCE DI KEDAI LELY YUMMY MENGGUNAKAN METODE DESIGN THINKING - Aprimavista, Laily Irana; Budianto, Alexius Endy; Ahsan, Moh (Prodi Teknik Informatika, Fakultas Sains dan Teknologi, 2025)
Design Thinking is a design process that focuses on user emphaty to understand real problems according (Irwinansyah et al, 2020). Problems that are not clearly defined will be resolved by understanding user needs, for example, selling fastfood products, and drinks at the Lely Yummy Shop which is in located Sukowilangun Village, Kalipare District. Malang Regency. This research designs the Figma application for the fastfood, and beverage sales business by considering the User Interface/User Experience at the Lely Yummy Shop, various kinds of problems, and solutions discussed. This research aims to determine the level of information service for customers, design layout designs in shop business sales, and understand the general description of Lely Yummy shop services using the Design Thinking Method. According to the term, the Design Thinking method is a human-centered design approach to solving problems, and introducing new innovations. The Design Thinking method includes 5 steps consisting of emphatize, define, ideate, prototype, and testing. The five steps in the design thinking method will of course be discussed in chapters 3, and 4 along with a project using the figma application by considering User Interface/User Experience in the business of selling fastfood, and drinks at Lely Yummy stores.